(3GdTaGA aj GdWH GdeSfO Yf GdeUWajs - (3GdJjaGTj , CMeO Hf jhSa Hf CMeO Hf CHj HcQ Hf MeOhf GdbjSj, TQa GdOjf,J (B651 (3g` s
(3ChdgG (B:s
(3hHYO ,aEfi deG bQCJ cJGH GdMGaX CHj fYSe , CMeO YHO Gddg GdCUagGfi GdPi hVYg ai GdCMGOjK GdWHjI hCKHJgG HCSGfjOgG eQahYI Zdi SjO GdHTQ GdTajY GdeTaY s
(3BNQgG (B:s
(3bGd (B: (3bGd QShd Gddg Udi Gddg Ydjg hSde (B:" (3aVd Ogf GdHfaSL Ydi SGFQ GdCOgGf caVdi Ydi SGFQ GdNdb (B" (3HGQO ai GdUja MGQ ai GdTJGA s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B273 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B2 - (3U (B208s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA WH (B- (3bSe GdcJGH GdKGfi (B- (3U (B141 ; (3eLdI eYgO GdeNWhWGJ (B- (3GdLRA (B5 - (3U (B286 s
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdeUQjI (B((3WH WdYJ (B85) s
Keywords: (3GdWHs